Efektivitas Salep Ekstrak Bambu Tali (Gigantochloa Apus) untuk Mengatasi Infeksi Sarcoptes Scabiei - Silvi Fatika Wulandari; Agus Darwanto; Dwi Setya Ningrum (Universitas Borneo Lestari, 2023)
Tali bamboo (Gigantochloa apus) is a source of flavonoids which are useful for health, including reducing the mite Sarcoptes scabiei in scabies pathogens. The aim of this study was to make an ointment from tali bamboo leaf extract with a white vaseline and salicylic acid base to treat scabies. The data collection method used experiments with the prevalence method using a sample of rabbits (Oryctolagus cuniculus) that had been infected with scabies. Data analysis used descriptive comparative analysis. Tali bamboo leaf extract ointment is made by combining tali bamboo leaf extract, vaseline, salicylic acid, and 0.05 ml of glycerin. Tali bamboo leaf extraction process was carried out using 96% ethanol solvent. The ointment has a cream form, brown color, scented with bamboo leaf extract with a pH of 6.5. The spreading power of the ointment was 3.5 cm and the adhesion was 3.66 seconds. The content of flavonoids in the ointment was 0.1633% w/w QE and phenolics 0.371% w/w GAE. The content of antioxidant compounds in 10 ppm of ointment is 10.09%. The content of antioxidant compounds in 10 ppm of ointment is 10.09%. Ointment has inhibitory power against gram positive bacteria 9 mm, 10 mm and 11 mm. The trial results showed that the use of tali bamboo leaf extract ointment was more effective in treating scabies in rabbits compared to wormectin, ivomec, gusanex, and cooking oil. At 72 hours and 168 hours after treatment with the use of tali bamboo leaf ointment, a significant decrease in the width of the wound was obtained with indicators of changes in the wound shrinking and drying. Meanwhile, at 240 hours, all samples were declared cured of scabies infection. Thus, tali bamboo leaf extract ointment is more effective in treating scabies infection in rabbits than wormectin, ivomec, gusanex and cooking oil.